Penggunaan Mat Serbuk Daun Kemangi (Ocimum sanctum) dan Mat Serbuk Daun Pandan Wangi (Pandanus amaryllifolius) Sebagai Repellent Nyamuk Aedes sp. - Ninda Ika Widanty; Lucky Herawati; Sarjito Eko Windarso (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
The controlling of Aedes sp. mosquitoes with anti-mosquitoes which containing synthetic insecti-cide continuously gives bad impact to human’s health, causes mosquitoes resistance as well as pollutes the environment. One safe and eco-friendly alternative solution to control Aedes sp. is by using basil leaves (Ocimum sanctum) and fragrant pandan leaves (Pandanus amaryllifolius) which contain natural insecticide as anti-mosquitoes electrical device. The aim of this study was to know the influence of the leaves as repellent for the mosquitoes by conducting and experi-ment with post test only with control group design. The study sample were 600 Aedes adult mos-quitoes bred from the eggs obtained from BBTKL PPM Yogyakarta for 10 repetition. The results of the study showed that 4 gram weighted mat made from basil leaves and 3,5 gram weighted mat made from fragrant pandan leaves, were able to repel 37,0 % and 63,5 % the mosquito, res-pectively. The result of one way anova test yielded p value less than 0,001; which can be inter-preted that the repellent ability between the two mats are statistically different, and those which made from fragrant pandan leaves gave best outcomes. Likewise, majority of the respondents (76,7 %) who were selected and appointed, also preferred the fragrant pandan leaves electric mat.